Application of High-Order Questions as an Objective Assessment Tool During Distance Learning (Journal of Educational Sciences, 2022)
The article discusses the impact of the pandemic on the quality of knowledge and the psychological state of students studying at the CIS accredited international Nazarbayev Intellectual School in UstKamenogorsk. The analysis was carried out on the example of biology, physics, and English in grade11. It was found that in the online learning environment, the principles of academic honesty on the partof students are not fully observed. For more honest results, it is necessary to use specialized programsthat block the desktop and limit time, etc. During the pandemic, the time allocated to each subject formastering the curriculum was halved, but the program itself was not reduced. These facts led to an aggravation of the psychological state of the students. It was found that during the pandemic, referrals to aschool psychologist increased by an average of 9%. The main problems on the part of the students arethe lack of live communication, family conflicts, and withdrawal. Most students have a problem withtime management. According to the research conducted, student activity falls from 40% to 24% duringoffline learning to 16% during online learning. The students’ mood is also reduced by 4%.Key words: pandemic, high-order questions, open-ended questions, online learning, stress resistance, academic integrity, communication skills.